Community Empowerment in Increasing Welfare Family Based on Local Potentials in Pakel and Garon Hamlet, Dompyong Village, Bendungan District, Trenggalek Regency - D. Tranggono; Tukimah; R. P. Tutiasri (Future Science)
Trenggalek Regency has a lot of natural potentials, which if given intensive attention from certain parties: Regency / Service Government and related agencies, as well as Universities through research and community service, it is possible to change the progress in Trenggalek. The purpose of University Students’ Community Service or KKN activities in this second year is to realize the first year’s plan which among other things; implementation of training and mentoring of cassava product-making, the process of making dairy products from local dairy-cow namely fresh drink of various flavours, as well as making modules / guidelines about cassava, maize and ginger cultivation techniques as raw materials for processed products. The results after training and mentoring in the product-making process of cassava chips and various flavours of fresh dairy products as well as counseling on Agricultural Cultivation Techniques are: (1) Intention and enthusiasm from Women Farmers Group (KWT) in developing local products in the village has increased (2) the ability of the KWT to produce superior products is getting better, (3) the farmers have understood the right procedure of farming techniques. Based on the previous results and conclusions, so the recommendation programs for the third year as follows: (1) Organizing capital development from Dompyong, (2) Establishing marketing network assistance if featured products can really be realized by the Women Farmers Group (KWT) , (3) Developing organic pesticides and fertilizers, as well as good agricultural cultivation techniques, and (4) Providing and developing Appropriate Technology (TTG; Teknologi Tepat Guna).